Postmortem Study of Head Injury in Fatal Road Traffic Accidents (Journal of Armed Forces Medical College, Bangladesh, 2010)
This study was conducted at the Dhaka Medical College (DMC) morgue among 100 postmortem cases of Road Traffic Accident (RTA) victims over a period of one year. The objective of this study was to find out incidences of head injury among the RTA victims along with other injuries and also to overview the present situation of RTA in the country. Out of 100 cases, 64% were male and 36% female. The highest incidence of RTA (28%) was observed among the age group 31 to 40 years. The highest number of victims were pedestrians (68%). Considering recorded causality by type of collision, hit pedestrian was the most common (39%), followed by head on collision (20%). Regarding injury pattern in different parts of body, all the victims had multiple abrasion and bruise, 90% had laceration, 78% had injury to brain and 77% victims had injury to abdominal organs like liver and spleen. In the skull, Linear/fissured fracture was the commonest type of fracture (36%), followed by comminuted fracture (18%). Temporal bone was observed most prone to be fractured (23%), followed by parietal bone (17%). Most of the victims had subdural haemorrhage (43%), followed by sub arachnoid haemorrhage (36%). Key words: Road traffic accident, head injury, postmortem. DOI: 10.3329/jafmc.v5i2.4579 JAFMC Bangladesh Vol.5(2) (December) 2009, pp.24-28